Alkohol legalization in United Arab Emirates’: Between local norms and global tolerance - Putra, Alfen Redho (Universitas Islam Malang, 2024)
This article departs from the phenomenon of tolerance by the United Arab Emirates towards global citizens who live through the policy of legalizing alcohol, which was previously an act that was criminalized by the government which was heavily influenced by Islamic values. This observation uses a qualitative method with a descriptive model that takes information from several previous literature as well as articles and reports in the media that directly discuss related phenomena. This research uses the concept of national interests as a thinking approach in finding answers regarding the strong reasons for the United Arab Emirates to implement tolerance through this policy. The results of the observations provide an answer that the reason the United Arab Emirates issued a policy of legalizing alcohol freely was as a form of real execution of the country which wants to build a new image as a world tolerant country that accepts the differences of its immigrant citizens, especially culturally living with alcohol which is seen as very contrary to local norms. This policy is of course influenced by the main factor of the United Arab Emirates as a tourist country which has a very large migrant population that exceeds its own local population. By using a national interest approach, of course there is a goal that makes the country implement this policy, which is none other than tourism purposes. Certainly this research will be an informant regarding the unique things implemented by the United Arab Emirates.